Description of Knowledge Contraception Aceptor Injection of 3 Months in Primary Health Care - Crisfabiani, Gracia; Indo Virawati, Dini; Satriani, Satriani (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: The use of contraceptives has increased in many parts of the world, especially in Asia and Latin America. The pattern of choosing contraceptives in (2020) shows that most voters choose to use the injection method at 72.9%), followed by pills at 19.4%. Knowledge of 3-month injection family planning is very much needed by suburban women. The problem that arises from the mother's lack of knowledge is that if contraceptives are used for a long period of time it can cause, mothers are often found with complaints of weight gain, in the long term it can cause obesity which can cause diseases between cholesterol and heart. Objectives: to determine the level of knowledge of injecting family planning acceptors about 3 months injectable family planning at the Linggang Tutung Public Health Center. Methods: type research is descriptive research. Total of sampel 32 sampel. Results and Discussion: Mother's characteristics are known based on age, education, and occupation. it is known that the knowledge level of injecting family planning acceptors is in good category with 24 respondents (75%). Conclusion: Almost all injectable family planning acceptors have a good level of knowledge. This shows that family planning acceptors have good knowledge and do not just use it, but know the meaning, benefits, workings, side effects, use of 3-month contraception.